Sonya Kovalevsky: The Russian Queen of Mathematics Post-Enlightenment - Sapunaru, Raquel Anna (2018)
The idea of this article is to disclose the main aspects of life and work of Sonya Kovalevsky, such as how she began her excellent disposition to learn science and how she overcame the barriers of the time to be able to follow scientific studies abroad and fulfill her dream of occupying a position in a European university. In order to reach my objective, a reflexive and systematic procedure was performed, in which the data were obtained through indirect documentation, that is, research of an existing bibliography, since it seeks to narrate and explain the history of a great mathematical character of the nineteenth century, little known of the public in general. It is, therefore, a compilation article, remembering that this type of study consists of orderly gathering the selected bibliography, combining it and extracting what is interesting for the accomplishment of the objective. As a result, I got an overview of the life and work of Sonya Kovalevsky, from her childhood to her early death in 1891, exploring her mathematic ability and writing talents.